TEM micrographs and EELS images of neutron, proton and self-ion irradiated Fe9Cr - Haley, J; Lozano-Perez, S; Roberts, S; Odette, G; London, A; de Moraes Shubeita, S; Wady, P (University of Oxford, 2020)
This data provides a comparison of the microstructure of a model Fe9Cr alloy subject to irradiation by neutrons, protons or self-ions. The micrographs contained are sufficient to calculate dislocation number densities, sizes, and nature; void number densities and sizes; and the chemical mapping obtained for analysis of chromium redistribution within the alloy.